Faktor Lingkungan Fisik yang Memengaruhi Kejadian Pneumonia Balita di Negara Berkembang Asia: Scoping Review - Salsabila, Nida Tahara; Sutiningsih, Dwi; Sakundarno, M. (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2026)
Background: Pneumonia remains one of the leading causes of morbidity and mortality among children under five in developing countries and is suspected to be associated with household physical environmental factors that have not been comprehensively examined in an integrated manner. Objective: This study aimed to map the scientific evidence on physical environmental factors associated with pneumonia among children under five in developing countries in Asia using a scoping review approach based on the PRISMA-ScR guidelines. Methods: Literature searches were conducted in the Scopus, PubMed, and Google Scholar databases from 2015 to 2025, with inclusion criteria focusing on primary research articles addressing children under five and physical environmental factors. A total of ten articles were included and analyzed descriptively. Results: The findings indicate that the most consistently associated household physical environmental factors with pneumonia among children under five include indoor air pollution from biomass fuels, inadequate household ventilation, overcrowding, and exposure to harmful gases such as carbon monoxide. In addition, poor natural lighting and high humidity were also reported to contribute to an increased risk of pneumonia. It was also found that immunization status and socioeconomic conditions influence the incidence of pneumonia. Conclusion: These findings indicate that pneumonia among children under five is a multifactorial isease influenced not only by household environmental conditions, but also by biological and socioeconomic factors. Overall, household physical environmental factors remain important determinants of pneumonia among children under five, although their impact may vary depending on contextual and supporting factors